Genome-wide Transcriptional Analysis of Tetrahymena thermophila Response to Exogenous Cholesterol - Najle, Sebastián Rodrigo (2020)
The ciliate Tetrahymena thermophila does not require sterols for growth and synthesizes pentacyclic triterpenoid alcohols, mainly tetrahymanol, as sterol surrogates. However, when sterols are present in the environment, T. thermophila efficiently incorporates and modifies them. These modifications consist of desaturation reactions at positions C5(6), C7(8), and C22(23), and de-ethylation at C24 of 29-carbon sterols (i.e. phytosterols). Three out of four of the enzymes involved in the sterol modification pathway have been previously identified. However, identification of the sterol C22 desaturase remained elusive, as did other basic aspects of this metabolism. To get more insights into this peculiar metabolism, we here perform a whole transcriptome analysis of T. thermophila in response to exogenous cholesterol. We found 356 T. thermophila genes to be differentially expressed after supplementation with cholesterol for 2 h. Among those that were upregulated, we found two genes belonging to the long spacing family of desaturases that we tentatively identified by RNAi analysis as sterol C22 desaturases. Additionally, we determined that the inhibition of tetrahymanol synthesis after supplementation with cholesterol occurs by a transcriptional downregulation of genes involved in squalene synthesis and cyclization. Finally, we identified several uncharacterized genes that are likely involved in sterols transport and signaling.